Prevalence and correlates of depression among pregnant adolescents in primary maternal care in Nigeria (2022)
To examine the prevalence as well as the clinical and psychosocial factors associated with depression and depression severity in pregnant adolescents. Participants were consecutively registered pregnant adolescents presenting to 30 selected primary maternal and child healthcare centers in Ibadan, Nigeria, who were screened for enrolment into an intervention trial for perinatal depression (depression defined as a score of ≥ 12 on the Edinburg Postnatal Depression Scale [EPDS] and met the DSM-IV diagnostic criteria for depression). Of the 1359 pregnant adolescents screened, 246 (18.1%) had depression. Mean age was 18.4 (sd 1.00), 58.9% were either married or cohabiting, 91.4% were primipara, and the mean gestational age was 23.8 weeks (sd 5.4 weeks). Food insecurity (going to bed hungry at least once in the previous week because there was no food to eat) was reported by 13.3%. In bivariate analysis, younger age, not living with a partner, unemployment, and food insecurity were associated with depression. In bivariate analysis, younger age, not living with a partner, unemployment and food insecurity were associated with depression, while younger age, being single and food insecurity were independently associated with being depressed in multivariate analysis. Severity of depression was related to age, higher anxiety and disability scores, lower quality of life scores across all domains and poorer attitudes towards pregnancy. Depression was associated with indices of higher social disadvantage among adolescents. Delaying childbearing and measures aimed at alleviating poverty may be important in preventing depression in this vulnerable group.